Reproductive pattern in the solanum mealybug, Phenacoccus solani: A new perspective - Jun Huang; Fuying Zhi; Juan Zhang; Muhammad Hafeez; Xiaowei Li; Jinming Zhang; Zhijun Zhang; Likun Wang; Yaobin Lu (PeerJ, 2020)
Background The reproductive pattern of most scale insects is ovoviviparity. The solanum mealybug, Phenacoccus solani (Hemiptera: Pseudococcidae), is known as a thelytokous parthenogenetic species, but there is still debate about the reproductive strategies of this species. Methods Here, we investigated the oviposition characteristics of P. solani and used scanning/transmission electron microscopy and RNA-seq to identify the differences between two types of eggs. Results We found that P. solani laid two types of eggs in one batch, with no significant difference in apparent size: one with eyespots that hatched and another without eyespots that failed to hatch. Furthermore, the physiological and molecular differences between the two types of eggs were highly significant. KEGG enrichment analysis revealed significant enrichment for the JAK-STAT, Notch, Hippo, and Wnt signaling pathways and dorsoventral axis formation, wax biosynthesis, cell cycle, insulin secretion, and nitrogen metabolism pathways. The results suggest that the embryo of the egg undergoes development inside the mother and only a short molting period outside the mother. Discussion Ovoviviparous species produce eggs and keep them inside the mother’s body until they are ready to hatch, and the offspring exits the egg shell during or immediately following oviposition. Therefore, we suggest that the reproductive pattern of P. solani can be described as ovoviviparity.